Light-transmitting film, its manufacturing method, and display device including same
The method of manufacturing a light-transmitting film with uniform filler dispersibility addresses the challenges of haze and mechanical strength in display device cover windows, achieving improved optical and mechanical performance through a hybrid mixing technique.
Patent Information
- Application Number
- JP2023500350
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-07
- Filing Date
- 2021-07-07
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-07-07
AI Technical Summary
Existing light-transmitting films used as cover windows in display devices face challenges in achieving uniform filler dispersibility, leading to issues with haze and mechanical properties, which affect their protective and optical performance.
A method for manufacturing a light-transmitting film involves producing a resin powder, dissolving it in a solvent, adding a filler dispersion, and mixing it with a resin solution to achieve uniform filler dispersibility, using a hybrid mixing technique that includes both solution-to-solution and solution-to-powder mixing, resulting in a film with a power law slope of -3.6 to -3.2 and excellent mechanical properties.
The resulting film exhibits improved filler dispersibility, reduced haze, enhanced mechanical strength, and optical clarity, making it suitable for protecting display devices while maintaining high light transmittance and flexibility.
Smart Images

Figure 0007620078000014 
Figure 0007620078000015 
Figure 0007620078000016
Abstract
Description
[Technical field]
[0001] The present invention relates to a light-transmitting film having excellent filler dispersibility, a method for producing the same, and a display device including the same. [Background technology]
[0002] In recent years, as display devices have become thinner, lighter, and more flexible, the use of a light-transmitting film instead of glass as a cover window has been considered. In order to use a light-transmitting film as a cover window of a display device, the light-transmitting film needs to have excellent properties such as hardness, abrasion resistance, and flexibility.
[0003] Transparent plastic films are being researched as light-transmitting films for cover windows of display devices. Among transparent plastic films, for example, polyimide-based films with high hardness are being researched as materials for cover windows of flexible display devices. Polyimide-based films are made of polyimide (PI)-based resins. Polyimide (PI)-based resins have insolubility, chemical resistance, heat resistance, radiation resistance, and low-temperature properties, and are used as automotive materials, aviation materials, spacecraft materials, insulating coating agents, insulating films, protective films, etc.
[0004] Meanwhile, a filler may be added to the light-transmitting film in order to provide the light-transmitting film with desired physical properties. The filler is preferably uniformly dispersed in the light-transmitting film. Summary of the Invention [Problem to be solved by the invention]
[0005] An object of one embodiment of the present invention is to provide a method for producing a light-transmitting film having excellent filler dispersion.
[0006] One embodiment of the present invention aims to provide a light-transmitting film that includes a filler that is uniformly dispersed within a light-transmitting matrix.
[0007] An object of one embodiment of the present invention is to provide a light-transmitting film having a power law slope in the range of −3.6 to −3.2 as determined by U-SAXS analysis.
[0008] An object of one embodiment of the present invention is to provide a light-transmitting film having excellent light transmittance and low haze by uniformly dispersing a filler.
[0009] An object of one embodiment of the present invention is to provide a light-transmitting film having a high Young's modulus by uniformly dispersing a filler in a light-transmitting matrix.
[0010] Another embodiment of the present invention aims to provide a polyimide-based film having excellent optical and mechanical properties, comprising a filler dispersed within a polyimide-based matrix so as to have an average particle scattering coefficient of 0.35 or less.
[0011] It is still another object of the present invention to provide a display device including a polyimide film having excellent filler dispersibility. [Means for solving the problem]
[0012] One embodiment of the present invention provides a method for manufacturing a light-transmitting film, the method including: preparing a light-transmitting resin powder; dissolving a first content of the light-transmitting resin powder in a first solvent to prepare a light-transmitting resin solution; preparing a filler dispersion in which a filler is dispersed in a second solvent; mixing the filler dispersion and the light-transmitting resin solution to prepare a first mixed liquid; and adding and dissolving a second content of the light-transmitting resin powder in the first mixed liquid to prepare a second mixed liquid.
[0013] The first content of the light-transmitting resin powder may be 0.5 to 10% by weight of the filler.
[0014] The method may further include adding a third solvent to the first mixture before adding the second content of the optically transparent resin powder to the first mixture.
[0015] The third solvent may be the same as the first solvent.
[0016] The second content of the optically transparent resin powder may be 10 to 200 times the first content.
[0017] The light-transmitting resin may include an imide repeat unit.
[0018] The light-transmitting resin may include an amide repeat unit.
[0019] Another embodiment of the present invention provides a light-transmitting film that includes a light-transmitting matrix and a filler dispersed in the light-transmitting matrix, and has a power law slope of -3.6 to -3.2 in a wave number range of 0.01 / Å to 0.1 / Å in an Ultra-Small Angle X-ray Scattering (U-SAXS) graph, in which scattering intensity is logarithmically plotted against wave number.
[0020] The filler includes silica (SiO2).
[0021] At least a part of the silica (SiO2) is surface-treated with an organic compound group having an alkoxy group.
[0022] The average particle size of the filler is 5 to 50 nm.
[0023] The content of the filler is 5 to 46% by weight based on the total weight of the light-transmitting film.
[0024] The average shortest adjacent distance between the fillers is 23 to 45 nm.
[0025] The light-transmitting film has a yellowness index of 3 or less.
[0026] The light-transmitting film has a haze of 1% or less.
[0027] The light-transmitting film has a light transmittance of 85% or more.
[0028] The light-transmitting film has a "Young's modulus" of 4.5 GPa or more and a "2% yield strength" of 95 MPa or more.
[0029] The light-transmitting matrix may include imide repeat units.
[0030] The light-transmitting matrix may include amide repeat units.
[0031] Yet another embodiment of the present invention provides a light-transmitting film comprising a light-transmitting matrix and a filler dispersed in the light-transmitting matrix, the filler having an average particle scattering coefficient (XA) of 0.35 or less, the average particle scattering coefficient (XA) being calculated according to the following Equation 1:
[0032] <Expression 1> TIFF0007620078000001.tif2158
[0033] In formula 1, X k is calculated from the following formula 2.
[0034] <Expression 2> X k =πD / λ k
[0035] In formula 1 and formula 2, k is an integer of 1 to 38, and in formula 2, λ k = (37 + k) × 10 nm, and D is the particle size of the filler measured by transmission electron microscopy (TEM).
[0036] The content of the filler may be 5 to 50% by weight based on the total weight of the light-transmitting film.
[0037] The light-transmitting film may have a light transmittance of 88% or greater.
[0038] The light-transmitting film may have a modulus of 5.0 GPa or more.
[0039] Yet another embodiment of the present invention provides a display device including a display panel and the light-transmitting film disposed on the display panel. Effect of the Invention
[0040] According to an embodiment of the present invention, a light-transmitting film having excellent filler dispersion can be manufactured.
[0041] Generally, when a filler is dispersed in a light-transmitting film, the haze of the light-transmitting film may decrease, but according to one embodiment of the present invention, the light-transmitting film has excellent filler dispersion and excellent haze characteristics, and the power law slope of the light-transmitting film according to U-SAXS analysis can be in the range of -3.6 to -3.2. Furthermore, the light-transmitting film according to one embodiment of the present invention can have excellent Young's modulus and excellent yield strength.
[0042] The light-transmitting film according to an embodiment of the present invention has excellent optical and mechanical properties, and therefore, when used as a cover window of a display device, it can effectively protect the display surface of the display device. [Brief description of the drawings]
[0043] [Figure 1] 1 is a schematic diagram of a light-transmitting film according to an embodiment of the present invention. [Diagram 2] 1 is a U-SAX graph of a light-transmitting film according to an embodiment of the present invention. [Diagram 3]FIG. 2 is a schematic diagram illustrating a dispersion state of a filler in a light-transmitting film according to an embodiment of the present invention. [Figure 4] 11 is a cross-sectional view of a portion of a display device according to another embodiment of the present invention. [Diagram 5] FIG. 5 is an enlarged cross-sectional view of part “P” in FIG. 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0044] Hereinafter, the embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the embodiments described below are presented for the purpose of illustration to help a clear understanding of the present invention, and are not intended to limit the scope of the present invention.
[0045] The shapes, sizes, ratios, angles, numbers, and the like disclosed in the drawings to explain the embodiments of the present invention are merely illustrative, and the present invention is not limited to the matters shown in the drawings. Throughout the specification, the same components may be referred to by the same reference numerals. In the description of the present invention, if it is determined that a detailed description of related known art may unnecessarily obscure the gist of the present invention, the detailed description will be omitted.
[0046] When the terms "including," "having," "made," etc. are used in this specification, other parts may be added unless the expression "only" is used. When an element is expressed in the singular, it includes the plural unless otherwise expressly stated. In addition, when analyzing an element, it is interpreted as including a margin of error even if there is no other express description.
[0047] When describing a positional relationship between two parts, for example "on", "at the top", "below", "to the side", etc., one or more other parts may be located between the two parts, unless the words "immediately" or "directly" are used.
[0048] Spatially relative terms such as "below," "beneath," "lower," "above," "upper," and the like may be used to easily describe the relationship of one element or component to another element or component as shown in the figures. Spatially relative terms should be understood as terms that include different orientations of elements in use or operation in addition to the orientation shown in the figures. For example, if an element shown in the figures is turned over, an element described as "below" or "beneath" another element may be placed "above" the other element. Thus, the exemplary term "below" can include either an orientation of below or above. Similarly, the exemplary term "upper" can include either an orientation of above or below.
[0049] In explaining temporal relationships, for example, when the temporal precedence is explained using terms such as "after," "following," "next to," or "before," it is possible to include cases where things are not consecutive, since the expressions "immediately" or "directly" are not used.
[0050] Although the terms "first", "second" and the like are used to describe various components, these components are not limited by the terms. The terms are used merely to distinguish one component from another. Therefore, the first component referred to below may be the second component within the technical concept of the present invention.
[0051] The term "at least one" should be understood to include all possible combinations of one or more of the associated items. For example, "at least one of the first, second, and third items" can mean not only the first, second, or third item, respectively, but also any possible combination of items from two or more of the first, second, and third items.
[0052] The respective features of the various embodiments of the present invention may be partially or fully combined or combined with each other, and various interlocking and driving techniques may be possible, and each embodiment may be implemented independently of each other or may be implemented together in association with each other.
[0053] FIG. 1 is a schematic diagram of a light-transmitting film 100 according to one embodiment of the present invention.
[0054] A light-transmitting film 100 according to one embodiment of the present invention includes a light-transmitting matrix 110 and a filler 120 dispersed in the light-transmitting matrix.
[0055] According to one embodiment of the present invention, the light-transmitting matrix 110 has light-transmitting properties. Furthermore, the light-transmitting matrix 110 may have flexible properties. For example, the light-transmitting matrix 110 may have bending properties, folding properties, and rollable properties.
[0056] The light-transmitting matrix 110 includes a light-transmitting resin. The light-transmitting matrix 110 may include, for example, imide repeat units. Additionally, the light-transmitting matrix 110 may include, for example, amide repeat units.
[0057] The light-transmitting matrix 110 according to an embodiment of the present invention may be prepared from monomer components including, for example, a dianhydride and a diamine. More specifically, the light-transmitting matrix 110 according to an embodiment of the present invention may have imide repeat units formed by the dianhydride and the diamine.
[0058] Additionally, the light-transmitting matrix 110 according to an embodiment of the present invention may include amide repeat units formed by a dicarbonyl compound and a diamine.
[0059] The light-transmitting matrix 110 according to an embodiment of the present invention may be manufactured from monomer components including dianhydride, diamine, and dicarbonyl compounds. Therefore, the light-transmitting matrix 110 according to an embodiment of the present invention may have imide repeat units and amide repeat units. An example of the light-transmitting matrix 110 having imide repeat units and amide repeat units is polyamide-imide resin.
[0060] Therefore, the light-transmitting matrix 110 according to an embodiment of the present invention may include a polyimide resin or a polyamide-imide resin. According to an embodiment of the present invention, a resin containing an imide repeat unit is called a polyimide-based resin. The polyimide-based resin includes polyimide resin and polyamide-imide resin.
[0061] According to one embodiment of the present invention, the light-transmitting resin used as the light-transmitting matrix 110 may have excellent mechanical and optical properties.
[0062] The light-transmitting matrix 110 may have a thickness sufficient for the light-transmitting film 100 to protect the display panel. For example, the light-transmitting matrix 110 may have a thickness of 10 to 100 μm. According to one embodiment of the present invention, the thickness of the light-transmitting matrix 110 may be the thickness of the light-transmitting film 100. According to one embodiment of the present invention, the light-transmitting film 100 may have a thickness of 10 to 100 μm.
[0063] The light-transmitting matrix 110 may have an average light transmittance of 85% or more in the visible light region and a yellowness index of 5 or less when measured with a UV spectrophotometer, based on a thickness of 10 to 100 μm.
[0064] The light-transmitting film 100 according to an embodiment of the present invention includes, for example, a polyimide-based film using a polyimide-based resin as the light-transmitting matrix 110. The polyimide-based film includes a polyimide film and a polyamide-imide film.
[0065] The filler 120 may be inorganic or organic. The filler 120 may have a particle shape. The filler 120 may include at least one of inorganic particles, organic particles, and organic-inorganic composite particles. According to an embodiment of the present invention, for example, an inorganic filler may be used.
[0066] According to an embodiment of the present invention, the filler 120 may include silica (SiO2). For example, silica (SiO2) particles, which are inorganic, may be used for the filler 120.
[0067] According to an embodiment of the present invention, at least a portion of the silica (SiO2) used in the filler 120 may be surface-treated. More specifically, surface-treated silica (SiO2) particles may be used in the filler 120.
[0068] According to an embodiment of the present invention, at least a portion of the silica (SiO2) used in the filler 120 may be surface-treated with an organic compound group having an alkoxy group. For example, silica (SiO2) particles surface-treated with at least one of substituted or unsubstituted alkylalkoxysilane and phenylalkoxysilane may be used in the filler 120.
[0069] Specifically, silica (SiO2) particles surface-treated with methylalkoxysilane, ethylalkoxysilane, or phenylalkoxysilane can be used for the filler 120. More specifically, silica (SiO2) particles surface-treated with trimethoxy(methyl)silane or phenyltrimethoxysilane can be used for the filler 120.
[0070] According to an embodiment of the present invention, the filler 120 may have unit structures represented by the following Chemical Formulas 1 to 6.
[0071] [ka]
[0072] [ka]
[0073] [ka]
[0074] [ka]
[0075] [ka]
[0076] [ka]
[0077] In Chemical Formula 1 to Chemical Formula 6, each R can independently be at least one of an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, and a phenyl group having 6 to 18 carbon atoms.
[0078] Hereinafter, a method for manufacturing the light-transmitting film 100 according to an embodiment of the present invention will be described. For convenience of explanation, the method for manufacturing the light-transmitting film 100 will be described mainly in an embodiment in which the light-transmitting film 100 is a polyimide-based film.
[0079] The light-transmitting film 100 according to an embodiment of the present invention can be manufactured by a hybrid mixing method that combines solution-to-solution mixing and solution-to-powder mixing.
[0080] According to one embodiment of the present invention, a method for manufacturing the light-transmitting film 100 includes the steps of preparing a light-transmitting resin powder, dissolving a first content of the light-transmitting resin powder in a first solvent to prepare a light-transmitting resin solution, preparing a filler dispersion in which a filler is dispersed in a second solvent, mixing the filler dispersion and the light-transmitting resin solution to prepare a first mixed liquid, and adding and dissolving a second content of the light-transmitting resin powder in the first mixed liquid to prepare a second mixed liquid.
[0081] The light-transmitting resin may include an imide repeat unit. The light-transmitting resin may include an amide repeat unit. According to an embodiment of the present invention, the light-transmitting resin may be, for example, a polyimide resin.
[0082] The filler 120 dispersion can be made by adding the filler particles to the second solvent and stirring.
[0083] The method for manufacturing the light-transmitting film 100 according to the embodiment of the present invention may further include a step of casting the second mixture liquid.
[0084] A casting substrate is used for casting. There is no particular limitation on the type of the casting substrate. The casting substrate may be a glass substrate, a stainless steel (SUS) substrate, a Teflon substrate, or the like. According to an embodiment of the present invention, the casting substrate may be, for example, a glass substrate.
[0085] According to one embodiment of the present invention, the light-transmitting resin powder is mixed with the filler dispersion in at least two portions.
[0086] Specifically, the first content in the light-transmitting resin powder is dissolved in a first solvent and mixed with the filler dispersion in the form of a light-transmitting resin solution. The first content of the light-transmitting resin powder may be 0.5 to 10% of the filler weight. More specifically, the first content of the light-transmitting resin powder may be in the range of 1 to 10% of the total weight of the filler 120.
[0087] The second content in the light-transmitting resin powder is added in a powder state. Specifically, the second content in the light-transmitting resin powder can be added in a powder state to a first mixed liquid obtained by mixing a filler dispersion and a light-transmitting resin solution.
[0088] The second content of the light-transmitting resin powder may be the total content of the light-transmitting resin powder used in the manufacture of the light-transmitting film 100 excluding the first content. For example, the second content may be 5 times or more, 10 times or more, or 50 times or more, of the first content. According to another embodiment of the present invention, the second content of the light-transmitting resin powder may be 100 times or more of the first content.
[0089] According to an embodiment of the present invention, the second content of the light-transmitting resin powder may be 10 to 200 times the first content. More specifically, the second content of the light-transmitting resin powder may be 60 to 200 times the first content.
[0090] According to an embodiment of the present invention, the method may further include adding a third solvent to the first mixed solution before adding the second content of the light-transmitting resin powder to the first mixed solution. The third solvent may be the same as or different from the first solvent. According to an embodiment of the present invention, the third solvent may be the same as the first solvent.
[0091] As the first solvent, DMAc (N,N-Dimethylacetamide) can be used. As the second solvent, DMAc (N,N-Dimethylacetamide) or MEK (Methyl Ethyl Ketone) can be used. As the third solvent, DMAc (N,N-Dimethylacetamide) can be used. However, one embodiment of the present invention is not limited thereto, and other known solvents can be used as the first solvent, the second solvent, and the third solvent.
[0092] According to one embodiment of the present invention, first, a part (first content) of the light-transmitting resin powder is dissolved in a solvent and then mixed with the filler dispersion liquid, thereby improving the dispersibility of the filler.
[0093] For reference, when an optically transparent resin powder is directly added to a filler dispersion liquid in which a filler is dispersed, the solvent instantaneously penetrates into the inside of the powder from the surface of the powder, and at this time, the concentration around the powder surface instantaneously increases, which may cause the filler to aggregate.
[0094] Meanwhile, according to one embodiment of the present invention, a light-transmitting resin solution in which a light-transmitting resin powder is dissolved is first added to a filler dispersion liquid containing a solvent, so that the polymer chains of the light-transmitting resin distributed among the filler particles can prevent the aggregation between the fillers. Even if the light-transmitting resin powder is further added thereafter (adding the second content), the aggregation between the fillers does not occur. This makes it possible to prevent the aggregation of the filler and improve the dispersibility of the filler.
[0095] According to one embodiment of the present invention, a light-transmitting film 100 containing a uniformly dispersed filler 120 can be manufactured by a hybrid mixing method in which solution-to-solution mixing and solution-to-powder mixing are performed in parallel.
[0096] According to an embodiment of the present invention, the degree of freedom between the filler 120 and the light-transmitting resin can be kept high, creating an environment that facilitates dispersion. As a result, the filler 120 and the light-transmitting resin can be bonded in a high degree of freedom state, and the light-transmitting film 100 in which the filler 120 is uniformly dispersed in the matrix 110 formed by the light-transmitting resin can be manufactured.
[0097] According to an embodiment of the present invention, silica particles can be used as the filler 120. The silica particles can be produced from, for example, tetraethyltriethoxysilane. For example, ethanol and tetraethyltriethoxysilane (TEOS, Si(OC2H5)4) are added to a reactor and stirred at room temperature, and NH4OH is added thereto and stirred. The reaction product obtained is filtered, washed with ethanol, and then dried under reduced pressure to produce silica particles [SiO2] having an average particle size of about 20 nm.
[0098] A silica dispersion can be used as the dispersion of the filler 120. The silica dispersion can be produced, for example, by adding dimethylacetamide (DMAc) and silica particles to a reactor and stirring the mixture.
[0099] The light-transmitting film 100 according to an embodiment of the present invention, which has excellent filler dispersion, has excellent mechanical and optical properties.
[0100] The light-transmitting film 100 according to an embodiment of the present invention has a power law slope of -3.6 to -3.2.
[0101] Specifically, in the light-transmitting film 100 according to one embodiment of the present invention, the power law slope of an ultra-small angle X-ray scattering (U-SAXS) graph, which logarithmically represents scattering intensity versus wavenumber, is −3.6 to −3.2 in the wavenumber range of 0.01 / Å to 0.1 / Å.
[0102] The ultra-small angle X-ray scattering (U-SAXS) graph is obtained by ultra-small angle X-ray scattering measurement.
[0103] An ultra-small angle X-ray scattering (U-SAXS) graph is a graph showing the wavenumber dependence of scattering intensity I of X-rays scattered by particles contained in a film when X-rays are incident on the film and the scattering angle 2θ is in the range of 5° or less. According to one embodiment of the present invention, the scattering angle 2θ can be adjusted by adjusting the distance between the sample and the detector. According to one embodiment of the present invention, the ultra-small angle X-ray scattering graph shows the wavenumber Q (unit: Å) dependence of scattering intensity I of X-rays scattered by particles contained in the film when X-rays are incident on the film and the scattering angle 2θ is in the range of 5° or less. -1 ) is the scattering intensity I. The wave number Q is calculated from 2π / λ, where λ is the wavelength of the X-ray.
[0104] For example, an ultra-small angle X-ray scattering graph can be obtained in the wave number range of 0.001 to 0.15 / Å, as shown in Fig. 2. In the ultra-small angle X-ray scattering graph according to one embodiment of the present invention, the scattering intensity I versus the wave number Q is expressed logarithmically.
[0105] According to one embodiment of the present invention, the slope of an ultra-small angle X-ray scattering graph showing the scattering intensity I versus the wave number Q in a logarithmic manner is measured in the wave number range of 0.01 / Å to 0.1 / Å, and the slope thus measured is the power law slope. In the light transmitting film 100 according to one embodiment of the present invention, the power law slope is −3.6 to −3.2.
[0106] Fig. 2 is an ultra-small angle X-ray scattering (U-SAXS) graph for the light-transmitting film 100 according to one embodiment of the present invention. Referring to Fig. 2, the ultra-small angle X-ray scattering (U-SAXS) graph shows the scattering intensity I logarithmically versus the wave number Q. Referring to Fig. 2, the power law slope of the ultra-small angle X-ray scattering (U-SAXS) graph is -3.4 in the wave number range of 0.01 / Å to 0.1 / Å.
[0107] Hereinafter, the slope of the ultra-small angle X-ray scattering (U-SAXS) graph in the wavenumber range of 0.01 / Å to 0.1 / Å will be simply referred to as the "power law slope."
[0108] According to one embodiment of the present invention, ultra-small angle X-ray scattering (U-SAXS) is performed using the 9A U-SAXS beamline at Pohang Accelerator Laboratory (Korea) under the following conditions to obtain an ultra-small angle X-ray scattering (U-SAXS) graph and the slope of the graph.
[0109] Wavenumber range: 0.001~2.5 / Å Energy (E): 19.70 keV Distance between sample and detector: 6.5m Exposure time: 30 seconds
[0110] Specifically, according to one embodiment of the present invention, a sample of the light-transmitting film 100 can be measured at the Pohang Light Source at Pohang Accelerator Laboratory (Pohang, Korea). The Pohang Light Source at Pohang Accelerator Laboratory (Pohang, Korea) includes a light source and a detector, and the sample is placed on the light path between the light source and the detector. According to one embodiment of the present invention, the sample is measured in transmission mode (T-SAXS). According to one embodiment of the present invention, a film consisting of only the light-transmitting matrix 110 without the filler 120 is used as a control for peak correction. The control allows the measurement peak of the light-transmitting film 100 sample to be corrected.
[0111] The magnitude of the scattering angle 2θ can be determined depending on the distance between the sample and the detector. According to one embodiment of the present invention, a sample is arranged in the synchrotron radiation accelerator at the Pohang Accelerator Laboratory (Pohang, Republic of Korea) so that the distance between the sample and the detector is 6.5 m, thereby realizing an ultra-small angle.
[0112] With regard to optical properties, the light-transmitting film 100 according to an embodiment of the present invention may have a yellowness index of 3 or less, a haze of 1% or less, and a light transmittance of 85% or more.
[0113] Furthermore, the light-transmitting film 100 according to an embodiment of the present invention may have excellent mechanical properties, such as a Young's modulus of 4.5 GPa or more and a "2% yield strength" of 95 MPa or more.
[0114] According to an embodiment of the present invention, the particle size, the content of the filler 120 and the particle spacing can be adjusted so that the light-transmitting film 100 has excellent optical and mechanical properties.
[0115] According to an embodiment of the present invention, the filler 120 may have an average particle size of 5 to 50 nm. If the average particle size of the filler 120 is less than 5 nm, the dispersibility of the filler 120 may decrease, and the filler 120 may aggregate. On the other hand, if the average particle size of the filler 120 exceeds 50 nm, the optical properties of the light-transmitting film 100 including the filler 120 may be degraded. For example, if the filler 120 having an average particle size exceeding 50 nm is excessively contained, the haze of the light-transmitting film 100 may increase.
[0116] Furthermore, if the average particle size of the filler 120 is less than 5 nm, the filler 120 may aggregate, reducing the mechanical strength of the light-transmitting film 100 in the portion where the filler 120 aggregates, thereby reducing the Young's modulus and 2% yield strength of the light-transmitting film 100. If the average particle size of the filler 120 exceeds 50 nm, the yield strength of the light-transmitting film 100 may be less than 95 MPa, reducing the mechanical strength.
[0117] Furthermore, when the average particle size of the filler 120 is less than 5 nm, the dispersibility of the filler 120 may decrease, and when the average particle size of the filler 120 is more than 50 nm, the interval between the filler 120 is not sufficiently secured. Therefore, in the wave number range of 0.01 / Å to 0.1 / Å on the ultra-small angle X-ray scattering (U-SAXS) graph, the power law slope may be less than -3.6 or more than -3.2.
[0118] According to another embodiment of the present invention, the filler 120 may have an average particle size of 10 to 20 nm, or may have an average particle size of 10 to 15 nm.
[0119] When the light-transmitting film 100 contains the filler 120 having a particle size in nanometers, the optical properties of the light-transmitting film 100 can be improved due to light scattering by the filler 120. Furthermore, when the light-transmitting film 100 contains the filler 120, the mechanical properties of the light-transmitting film 100 can be improved.
[0120] According to one embodiment of the present invention, the content of the filler 120 may be in the range of 5 to 50 weight % with respect to the total weight of the light-transmitting film 100. More specifically, in an embodiment for setting the power law slope in the range of -3.6 to -3.2, the content of the filler 120 may be in the range of 5 to 46 weight % with respect to the total weight of the light-transmitting film 100.
[0121] If the content of the filler 120 is less than 5 wt % with respect to the total weight of the light-transmitting film 100, the light scattering effect of the filler 120 may be minimal, and there may be little improvement in the light transmittance of the light-transmitting film 100. Also, if the content of the filler 120 is less than 5 wt % with respect to the total weight of the light-transmitting film 100, the improvement in the Young's modulus and 2% yield strength of the light-transmitting film 100 may be minimal.
[0122] On the other hand, when the content of the filler 120 exceeds 50% by weight with respect to the total weight of the light-transmitting film 100, the dispersibility of the filler 120 decreases, and the haze of the light-transmitting film 100 may decrease, and the excess filler 120 may block light and reduce the light transmittance of the light-transmitting film 100. More specifically, when the content of the filler 120 exceeds 46% by weight with respect to the total weight of the light-transmitting film 100, the power law slope of the light-transmitting film 100 may deviate from the range of -3.6 to -3.2, and the haze of the light-transmitting film 100 may decrease, and the light transmittance of the light-transmitting film 100 may decrease.
[0123] According to an embodiment of the present invention, the average shortest adjacent distance between the fillers 120 is 23 to 45 nm. More specifically, the average distance between the two closest adjacent fillers 120 may be 23 to 45 nm.
[0124] On the other hand, when the average shortest adjacent distance between the fillers 120 is less than 23 nm, in the wavenumber range of 0.01 / Å to 0.1 / Å in an ultra-small angle X-ray scattering (U-SAXS) graph in which the scattering intensity is logarithmically expressed versus wavenumber, the power law slope is less than −3.6 or exceeds −3.2, and the haze of the light-transmitting film 100 decreases.
[0125] On the other hand, if the average shortest adjacent distance between the fillers 120 exceeds 45 nm, the light scattering effect of the fillers 120 is so small that the effect of improving the light transmittance of the light-transmitting film 100 may be hardly observed.
[0126] FIG. 3 is a schematic diagram illustrating the dispersion state of the filler 120 in the light-transmitting film 100 according to one embodiment of the present invention.
[0127] According to an embodiment of the present invention, the particle size of the filler 120 and the distance between the fillers 120 can be measured or calculated using a Transmission Electron Microscope (TEM) photograph of the light-transmitting film 100 .
[0128] Referring to FIG. 3, some of the fillers 120 are dispersed apart from each other, but some form aggregates. In FIG. 3, "Group A" indicates fillers 120 that form aggregates. The shortest distance between fillers 120 that form aggregates such as "Group A" in FIG. 3 is not 20 nm. On the other hand, unlike the fillers 120 in "Group A", the shortest distance between fillers 120 that are dispersed without agglomeration (parts other than Group A) is 20 nm or more. It can be said that the fewer the number of fillers 120 that form aggregates such as "Group A" in FIG. 3, the more uniformly the fillers 120 are dispersed in the light-transmitting film 100.
[0129] When the amount of filler 120 forming aggregates such as "Group A" in FIG. 3 is small, the power law slope of the ultra-small angle X-ray scattering (U-SAXS) graph, in which the scattering intensity is logarithmically plotted against the wavenumber, is in the range of -3.6 to -3.2 in the wavenumber range of 0.01 / Å to 0.1 / Å, and the light-transmitting film 100 can have low haze.
[0130] In general, when the filler 120 is included and cannot be dispersed sufficiently uniformly, the optical properties of the light-transmitting film 120 may be degraded, such as a decrease in light transmittance and an increase in haze, if the filler 120 is included and cannot be dispersed sufficiently uniformly. However, according to an embodiment of the present invention, by setting the power law slope of the light-transmitting film 120 to -3.6 to -3.2 in the wave number range of 0.01 / Å to 0.1 / Å in an ultra-small angle X-ray scattering (U-SAXS) graph, an increase in haze of the light-transmitting film 120 can be prevented, and a decrease in light transmittance can be prevented.
[0131] According to one embodiment of the present invention, the power law slope of the light-transmitting film 100 is −3.6 to −3.2 in the wavenumber range of 0.01 / Å to 0.1 / Å in an ultra-small angle X-ray scattering (U-SAXS) graph, which logarithmically represents scattering intensity versus wavenumber, and the light-transmitting film 100 may have a light transmittance of 85% or more, or 89% or more, or 90% or more, or 91% or more, and a yellowness index of 3.0 or less, or 1.0 or less.
[0132] According to one embodiment of the present invention, the power law slope of the light-transmitting film 100 is set to −3.6 to −3.2, so that the light-transmitting film 100 can have a yellowness index of 3 or less.
[0133] Furthermore, according to one embodiment of the present invention, the light-transmitting film 100 may have a haze of 1% or less.
[0134] Furthermore, according to one embodiment of the present invention, the light-transmitting film 100 has a power law slope of -3.6 to -3.2 in the wavenumber range of 0.01 / Å to 0.1 / Å in an ultra-small angle X-ray scattering (U-SAXS) graph, and has a Young's modulus of 4.5 GPa or more and a 2% yield strength of 95 MPa or more.
[0135] According to another embodiment of the present invention, the fillers 120 dispersed in the light-transmitting matrix 110 may have an average particle scattering coefficient (XA) of 0.35 or less.
[0136] The average particle scattering coefficient XA of the filler 120 is calculated by the following Equation 1.
[0137] <Expression 1> TIFF0007620078000008.tif2158
[0138] X in Equation 1 k can be calculated from the following equation 2.
[0139] <Expression 2> X k=πD / λ k
[0140] In formulas 1 and 2, k is an integer of 1 to 38.
[0141] In addition, in Equation 2, λ k = (37 + k) × 10 nm, and D is the particle size of the filler 120 calculated by transmission electron microscopy (TEM).
[0142] According to another embodiment of the present invention, the particle diameter of the filler 120 is the size of the particles of the filler 120. In another embodiment of the present invention, D is equal to the average particle diameter of the filler 120 calculated by a transmission electron microscope (TEM). More specifically, the particle size "D" in Equation 2 is the average particle diameter of the filler 120 calculated from an image taken by a transmission electron microscope (TEM).
[0143] According to another embodiment of the present invention, the particle size D of the filler 120 applied to Equation 2 may be different from the actual particle size of the filler 120 used in manufacturing the light-transmitting film 100. For example, when two or more fillers 120 are clustered or overlapped with each other along the observation direction of a transmission electron microscope (TEM) in the light-transmitting matrix 110, the clustered or overlapped two or more fillers 120 may appear as one particle in a clumped state in an image taken by the transmission electron microscope (TEM). As a result, the actual particle size of the filler 120 may differ from the average particle size D of the filler 120 calculated from the image taken by the transmission electron microscope (TEM).
[0144] According to another embodiment of the present invention, in the process of calculating the average particle scattering coefficient of the filler 120, the size of the particles of the filler 120 is calculated from an image taken by a transmission electron microscope (TEM). For example, the size of the particles of the filler 120 can be obtained in the following manner.
[0145] <Measurement equipment> Transmission electron microscope (TEM) (Manufacturer: Jeol / Model name: JEM-2100F)
[0146] <Measurement conditions> Accelerating voltage: 200 kV, magnification: 20,000x (20K)
[0147] <Cross-section processing> Microtome (Manufacturer: Leica / Model name: EM UC7) SPEED(mm / s):1mm / s FEED(nm):120nm Knife: DiATOME / Ultra 35 degrees
[0148] <Calculation method> Analyze using ImageJ as the image analysis program as follows.
[0149] 1) In Image type, switch to 8bit.
[0150] 2) In Process, set the noise to 100 via "Find maxima", set Output type to "Maxima within tolerance", and switch to "Exclude edge maxima" and "Light background".
[0151] 3) Perform "Fill holes" in Process Binary.
[0152] 4) Select “Watershed” from the Binary menu of Process.
[0153] 5) Drag the Rectangle and set the Area to 2250000~2500000 (excluding the area with the scale bar).
[0154] 6) Go to "Analyze" and select "Analyze particles". size(pixel 2):200-infinity, Circularity:0.0~1.0 The area of each particle is summed and divided by the number of particles to obtain the "average particle area," which corresponds to the average number of pixels each filler occupies in a transmission electron microscope (TEM) image.
[0155] 7) From the image obtained by a transmission electron microscope (TEM), the scale bar is measured with a straight segment to determine the "length per pixel (nm)". The length per pixel can be expressed in nm (nm / pixel). The "length per pixel (nm)" corresponds to the actual length of one side of the square pixels that make up the image captured by the transmission electron microscope (TEM). Therefore, the actual area of one pixel is [length per pixel (nm)] 2 It can be said that:
[0156] 8) The average particle area (pixel) obtained in “6”)” is converted to an area in metric units (SI units) using the length per pixel in “7”) to obtain the average particle size.
[0157] In an image obtained by a transmission electron microscope (TEM), the average number of pixels occupied by one filler is the "average particle area," and the actual area of one square pixel is (length per pixel) 2 Therefore, the area of the filler calculated from the image obtained by transmission electron microscope (TEM) is "(average particle area) x (length per pixel)" 2 According to another embodiment of the present invention, when the filler 120 is said to be spherical, the two-dimensional area of the filler 120 is "πr 2 =π(average particle size / 2) 2 "It can be said that.
[0158] Therefore, the average particle size of the filler 120 can be calculated by the following formula 3.
[0159] <Expression 3> JPEG0007620078000009.jpg15170
[0160] For example, the average particle area (pixel^2) of all particles obtained in "6)" = 900 pixels 2 When the length per pixel obtained in "7)" is 500 / 933 nm, the average particle size can be calculated as follows:
[0161] Average particle size (nm) = 2 * [(average particle area / π) * (length per pixel) 2 ] 1 / 2 = 2*[(900 / π)*(500 / 933) 2 ] 1 / 2 = 18.14 nm
[0162] The average particle size of the filler 120 calculated using transmission electron microscopy (TEM) and ImageJ can be used as the size D of the filler 120 particles.
[0163] Using the particle size D of the filler 120 thus obtained, the average particle scattering coefficient of the filler 120 is calculated according to Equations 1 and 2.
[0164] According to another embodiment of the present invention, when the filler 120 dispersed in the light-transmitting matrix 110 has an average particle scattering coefficient XA of 0.35 or less, the filler 120 is uniformly dispersed, and the light-transmitting film 100 can have excellent optical properties. In addition, when the filler 120 is dispersed in the light-transmitting matrix 110 with an average particle scattering coefficient XA of 0.35 or less, the effect of improving the mechanical properties of the light-transmitting film 100 can be maximized.
[0165] If the average particle scattering coefficient XA of the filler 120 exceeds 0.35, scattering may occur in the visible light region, decreasing the light transmittance of the light-transmitting film 100. As a result, a problem occurs in that the optical properties of the light-transmitting film 100 are deteriorated.
[0166] More specifically, according to another embodiment of the present invention, the filler 120 may have an average particle scattering coefficient of 0.1 or more. When the average particle scattering coefficient of the filler 120 is 0.1 or more, scattering is small in the visible light region, and the decrease in the light transmittance of the light-transmitting film 100 caused by the filler 120 can be suppressed. In addition, when the average particle scattering coefficient of the filler 120 is 0.1 or more and 0.35 or less, and the refractive index of the filler 120 itself is small, the refractive index of the filler 120 itself is reflected in the light-transmitting matrix 110, which may result in an improvement in the light transmittance due to a decrease in the reflectance of the light-transmitting film 100, and there is an advantage in that the yellowness of the light-transmitting film 100 is reduced due to the Rayleigh scattering effect.
[0167] According to another embodiment of the present invention, the filler 120 may have an average particle scattering coefficient of 0.07 to 0.35.
[0168] According to another embodiment of the present invention, the filler 120 may have an average particle scattering coefficient of 0.17 to 2.0.
[0169] According to another embodiment of the present invention, there is no particular limitation on the size or content of the filler 120. According to another embodiment of the present invention, the size and content of the filler 120 of the light-transmitting film 100 may be adjusted in consideration of the optical properties and mechanical properties.
[0170] According to another embodiment of the present invention, the filler 120 may have an average particle size of 5 to 50 nm.
[0171] If the average particle size of the filler 120 is less than 5 nm, the number of particles increases significantly relative to the same content, and the dispersibility of the filler 120 decreases due to the increase in relative surface area, which may cause the filler 120 to aggregate. On the other hand, if the average particle size of the filler 120 exceeds 50 nm, the optical properties of the light-transmitting film 100 containing the filler 120 may decrease. For example, if an excessive amount of filler 120 having an average particle size exceeding 50 nm is contained, the light transmittance of the light-transmitting film 100 may decrease and the haze may increase.
[0172] Furthermore, if the average particle size of the filler 120 is less than 5 nm, the mechanical strength of the light-transmitting film 100 may decrease in the portion where the filler 120 aggregates due to aggregation of the filler 120. As a result, the modulus of the light-transmitting film 100 can be decreased, and the mechanical strength can be decreased accordingly.
[0173] According to another embodiment of the present invention, when the filler 120 is added, appropriate light scattering occurs due to the filler 120, thereby improving the optical properties of the light-transmitting film 100. In order to enhance the light scattering effect, the content of the filler 120 contained in the light-transmitting film 100 can be adjusted.
[0174] According to another embodiment of the present invention, the content of the filler 120 may be in the range of 5 to 50% by weight with respect to the total weight of the light-transmitting film 100. More specifically, the content of the filler 120 with respect to the total weight of the light-transmitting film 100 may be adjusted to 5 to 40% by weight.
[0175] If the content of the filler 120 is less than 5% by weight relative to the total weight of the light-transmitting film 100, the light scattering effect of the filler 120 is minimal, there is almost no improvement in the light transmission of the light-transmitting film 100, and the effect of improving the modulus of the light-transmitting film 100 is also small.
[0176] On the other hand, if the content of the filler 120 exceeds 50% by weight based on the total weight of the light-transmitting film 100, the dispersibility of the filler 120 may decrease, which may result in a decrease in the haze of the light-transmitting film 100, and the excess filler 120 may cause agglomeration of the filler 12, which may block light and reduce the light transmittance of the light-transmitting film 100.
[0177] According to another embodiment of the present invention, by adjusting the content and particle size of the filler 120 and improving the dispersion method, the average particle scattering coefficient of the filler 120 dispersed in the light-transmitting matrix 110 is set to 0.35 or less, thereby preventing an increase in haze of the light-transmitting film 120 and preventing a decrease in light transmittance.
[0178] According to another embodiment of the present invention, the light-transmitting film 100 may have a yellowness index of 3 or less. More specifically, the light-transmitting film 100 according to another embodiment of the present invention may have a yellowness index of 2.0 or less, or may have a yellowness index of 1.0 or less.
[0179] According to another embodiment of the present invention, the light-transmitting film 100 may have a haze of 1% or less. More specifically, the light-transmitting film 100 according to another embodiment of the present invention may have a haze of 0.9% or less.
[0180] Furthermore, according to another embodiment of the present invention, the light-transmitting film 100 may have a light transmittance of 88% or more. More specifically, the light-transmitting film 100 according to another embodiment of the present invention may have a light transmittance of 89% or more, 90% or more, or 91% or more.
[0181] According to another embodiment of the present invention, the average particle scattering coefficient of the filler 120 dispersed in the light-transmitting matrix 110 is set to 0.35 or less, so that the light-transmitting film 100 can have a modulus of 5.0 GPa or more.
[0182] FIG. 4 is a cross-sectional view of a portion of a display device 200 according to another embodiment of the present invention, and FIG. 5 is an enlarged cross-sectional view of a portion "P" in FIG.
[0183] Referring to FIG. 4, a display device 200 according to another embodiment of the present invention includes a display panel 501 and a light-transmitting film 100 on the display panel 501 .
[0184] 4 and 5, a display panel 501 includes a substrate 510, a thin film transistor (TFT) on the substrate 510, and an organic light emitting element 570 connected to the thin film transistor (TFT). The organic light emitting element 570 includes a first electrode 571, an organic light emitting layer 572 on the first electrode 571, and a second electrode 573 on the organic light emitting layer 572. The display device 200 shown in FIGS. 4 and 5 is an organic light emitting display device.
[0185] The substrate 510 can be made of glass or plastic. Specifically, the substrate 510 can be made of plastic such as a light-transmitting resin or a light-transmitting film. Although not shown, a buffer layer can be disposed on the substrate 510.
[0186] The thin film transistor (TFT) is disposed on a substrate 510. The thin film transistor (TFT) includes a semiconductor layer 520, a gate electrode 530 insulated from the semiconductor layer 520 and overlapping at least a portion of the semiconductor layer 520, a source electrode 541 connected to the semiconductor layer 520, and a drain electrode 542 spaced apart from the source electrode 541 and connected to the semiconductor layer 520.
[0187] 5, a gate insulating film 535 is disposed between a gate electrode 530 and a semiconductor layer 520. An interlayer insulating film 551 may be disposed on the gate electrode 530, and a source electrode 541 and a source electrode 542 may be disposed on the interlayer insulating film 551.
[0188] The planarization film 552 is disposed on the thin film transistor TFT to planarize the upper portion of the thin film transistor TFT.
[0189] The first electrode 571 is disposed on the planarization film 552. The first electrode 571 is connected to a thin film transistor (TFT) via a contact hole provided in the planarization film 552.
[0190] The bank layer 580 is disposed on a part of the first electrode 571 and the planarization film 552 to define a pixel region or a light-emitting region. For example, the bank layer 580 can be disposed in a matrix structure in a boundary region between a plurality of pixels to define a pixel region by the bank layer 580.
[0191] The organic light emitting layer 572 is disposed on the first electrode 571. The organic light emitting layer 572 may also be disposed on the bank layer 580. The organic light emitting layer 572 may include one light emitting layer, or may include two light emitting layers stacked one above the other. The organic light emitting layer 572 may emit light having any one of red, green, and blue colors, and may emit white light.
[0192] A second electrode 573 is disposed on the organic light-emitting layer 572 .
[0193] The first electrode 571, the organic light emitting layer 572, and the second electrode 573 may be stacked to form the organic light emitting element 270.
[0194] Although not shown, when the organic light emitting layer 572 emits white light, each pixel may include a color filter for filtering the white light emitted from the organic light emitting layer 572 by wavelength. The color filter is formed on the path of light travel.
[0195] A thin film encapsulation layer 590 may be disposed on the second electrode 573. The thin film encapsulation layer 590 may include at least one organic film and at least one inorganic film, and the at least one organic film and the at least one inorganic film may be alternately disposed.
[0196] A light-transmitting film 100 is disposed on a display panel 501 having the above-mentioned laminated structure. The light-transmitting film 100 includes a light-transmitting matrix 110 and a filler 120 dispersed in the light-transmitting matrix 110.
[0197] The present invention will be described in more detail below with reference to Production Examples and Examples, however, the present invention is not limited to the Production Examples and Examples described below.
[0198] <Production Example 1: Production of Light-Transmitting Polymer Solid> A 1L reactor equipped with a stirrer, nitrogen injector, dropping funnel, temperature controller and cooler was filled with 776.655g of DMAc (N,N-Dimethylacetamide) while passing nitrogen through it, and the temperature of the reactor was set to 25°C, and 54.439g (0.17 mol) of TFDB was dissolved and the solution was maintained at 25°C. 15.005g (0.051 mol) of BPDA was added to the solution and stirred for 3 hours to completely dissolve BPDA, and then 22.657g (0.051 mol) of 6FDA was added and completely dissolved. The temperature of the reactor was lowered to 10°C, and 13.805g (0.068 mol) of TPC was added, and the mixture was reacted at 25°C for 12 hours to obtain a polymer solution with a solid concentration of 12% by weight.
[0199] 17.75g of pyridine and 22.92g of acetic anhydride were added to the obtained polymer solution and stirred for 30 minutes, then stirred again at 70°C for 1 hour and cooled to room temperature. 20L of methanol was added to the obtained polymer solution to precipitate a solid. The precipitated solid was filtered and pulverized, washed again with 2L of methanol, and dried at 100°C in vacuum for 6 hours to obtain a powdered light-transmitting polymer solid. The light-transmitting polymer solid produced here is a solid of polyimide resin. More specifically, the light-transmitting polymer solid produced in Production Example 1 is a powder of a polyamide-imide polymer solid, which corresponds to a light-transmitting resin powder.
[0200] <Example 1-1> A 1 L reactor was filled with 31.88 g of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 0.32 g (first content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to produce a liquid light-transmitting resin solution.
[0201] Another 1 L reactor was filled with 32.20 g of silica dispersion 1A (DMAC-ST, Nissan Chemical Corporation), which was prepared by dispersing silica particles having an average particle size of 10 to 15 nm in a DMAc (N,N-dimethylacetamide) solution (second solvent) at a content of 20 wt %, and then, while maintaining the temperature of the reactor at 25°C, the liquid light-transmitting resin solution prepared above was slowly added thereto using a cylinder pump for 1 hour to prepare a first mixture in which the silica dispersion and the light-transmitting resin solution were mixed.
[0202] 377.96 g of DMAc as a third solvent was added to the first mixed solution and stirred, and 64.08 g (second content) of polyamide-imide (light-transmitting resin powder) in the form of solid powder produced in Preparation Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0203] The obtained second mixture liquid was cast. A casting substrate is used for casting. There is no particular limitation on the type of the casting substrate. The casting substrate may be a glass substrate, a stainless steel (SUS) substrate, a Teflon (registered trademark) substrate, or the like. In one embodiment of the present invention, the casting substrate may be, for example, an organic substrate.
[0204] Specifically, the obtained second mixed liquid was applied and cast onto a glass substrate, and then dried with hot air at 130°C for 30 minutes to produce a film. The produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0205] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0206] As a result, a light-transmitting film 100 having a thickness of 80 μm was completed, which includes a light-transmitting matrix 110 and silica-based fillers 120 dispersed in the light-transmitting matrix. Here, the light-transmitting matrix 110 is made of a polyimide-based resin and has a film shape.
[0207] <Example 1-2> A 1 L reactor was filled with 70.51 g of DMAc (first solvent), and the reactor temperature was kept at 10° C. while stirring for a certain period of time. Then, 0.71 g (first content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred for 1 hour, and the temperature was raised to 25° C. to produce a liquid light-transmitting resin solution.
[0208] Another 1 L reactor was charged with 118.7 g of silica dispersion 1A (DMAC-ST, Nissan Chemical Co., Ltd.), and the temperature of the reactor was kept at 25° C. while the liquid light-transmitting resin solution prepared above was slowly added thereto using a cylinder pump for 1 hour to prepare a first mixture of the silica dispersion and the light-transmitting resin solution.
[0209] A second mixture was prepared by adding 144.29 g of DMAc as a third solvent to the first mixture and stirring, and then adding 74.34 g (second content) of the solid powder polyamide-imide (light-transmitting resin powder) prepared in Preparation Example 1 and stirring. The second mixture is a light-transmitting resin solution in which silica particles are dispersed.
[0210] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 130° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0211] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0212] As a result, a light-transmitting film 100 having a thickness of 80 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0213] <Example 1-3> A 1 L reactor was filled with 78.53 g of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 0.79 g (first content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to produce a liquid light-transmitting resin solution.
[0214] Another 1 L reactor was filled with 39.66 g of silica dispersion 1B (MEK-ST-40, Nissan Chemical Co., Ltd.), which was prepared by dispersing silica particles having an average particle size of 10 to 15 nm in an MEK (methyl ethyl ketone) solution (second solvent) at a content of 40 weight %, and then, while maintaining the temperature of the reactor at 25°C, the liquid light-transmitting resin solution prepared above was slowly added thereto using a cylinder pump for 1 hour, thereby preparing a first mixture in which the silica dispersion and the light-transmitting resin solution were mixed.
[0215] 244.79 g of DMAc as a third solvent was added to the first mixed solution and stirred, and 52.09 g (second content) of polyamide-imide (light-transmitting resin powder) in the form of solid powder produced in Production Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0216] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 130° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0217] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0218] As a result, a light-transmitting film 100 having a thickness of 80 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0219] <Example 1-4> A 1 L reactor was filled with 36.81 g of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 0.37 g (first content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to produce a liquid light-transmitting resin solution.
[0220] Another 1 L reactor was charged with 92.95 g of silica dispersion 1B (MEK-ST-40, Nissan Chemical Industries, Ltd.), and the temperature of the reactor was kept at 25° C. while the liquid light-transmitting resin solution prepared above was slowly added thereto using a cylinder pump for 1 hour to prepare a first mixture of the silica dispersion and the light-transmitting resin solution.
[0221] 295.46 g of DMAc, a third solvent, was added to the first mixed solution and stirred, and 61.60 g (second content) of polyamide-imide (light-transmitting resin powder) in the form of solid powder produced in Production Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0222] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 130° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0223] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0224] As a result, a light-transmitting film 100 having a thickness of 80 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0225] <Comparative Example 1-1> The light-transmitting film according to Comparative Example 1 was produced by a solution-powder mixing method.
[0226] Specifically, a 1L reactor was filled with 219.48g of DMAc and 163.82g of silica dispersion 1C (PGM-ST, Nissan Chemical Co., Ltd.) in which silica particles with an average particle size of 10 to 15 nm were dispersed at a content of 30% by weight in a propylene glycol monomethyl ether (PGME) solution as a silica dispersion, and the temperature of the reactor was kept at 10°C and stirred for a certain period of time. Then, 55.85g of the solid powder polyamide-imide produced in Production Example 1 was added and stirred for 1 hour, and the temperature was raised to 25°C to obtain a light-transmitting resin solution in which silica particles were dispersed.
[0227] The obtained optically transparent resin solution with the silica particles dispersed therein was cast by coating it onto a glass substrate and dried with hot air at 130°C for 30 minutes to produce a film. The produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0228] The frame with the film fixed was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, then slowly cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was again heat-treated at 250°C for 5 minutes to produce a light-transmitting film with a thickness of 80 μm.
[0229] <Comparative Example 1-2> A light-transmitting film having a thickness of 80 μm was produced by repeating the same steps as in Comparative Example 1, except that 361.71 g of DMAc and 50.58 g of polyamide-imide solid powder were used, and 25.29 g of Silica Dispersion 1D (MEK-ST-L, Nissan Chemical Co., Ltd.), in which silica particles having an average particle size of 45 nm were dispersed at 30 wt% in a methyl ethyl ketone (MEK) solution, was used as the silica dispersion.
[0230] <Measurement example> The light-transmitting films produced in Examples 1-1 to 1-4 and Comparative Examples 1-1 and 1-2 were subjected to the following measurements.
[0231] (1) Ultra-small angle X-ray scattering (U-SAXS) graph and power law slope
[0232] Ultra-small angle X-ray scattering (U-SAXS) was performed under the following conditions using the 9A U-SAXS beamline at the Pohang Accelerator Laboratory (Korea) as the U-SAXS measurement device, and a U-SAXS graph was obtained. The slope of the graph was calculated in the wavenumber range of 0.01 / Å to 0.1 / Å from the obtained graph, and the power law slope value was obtained.
[0233] Wavenumber range: 0.001~2.5 / Å Energy (E): 19.70 keV Distance between sample and detector: 6.5m Exposure time: 30 seconds
[0234] (2) Light transmittance (%): The average light transmittance at wavelengths of 360 to 740 nm was measured using a Spectrophotometer (CM-3700D, KONICA MINOLTA) in accordance with standard ASTM E313.
[0235] (3) Yellowness: Yellowness was measured according to standard ASTM E313 using a Spectrophotometer (CM-3700D, KONICA MINOLTA).
[0236] (4) Haze: The manufactured light-transmitting film was cut into a piece of 50 mm x 50 mm, and was measured five times according to ASTM D1003 using a haze meter (model name: HM-150) made by MURAKAMI, and the average value was taken as the haze value.
[0237] (5) Interparticle distance: The distance between the fillers 120 was measured using a transmission electron microscope (TEM) photograph of a light-transmitting film.
[0238] (6) Young's modulus and 2% yield strength: Young's modulus and 2% yield strength of the light-transmitting film were measured using an Instron universal tensile tester according to the ASTM D885 method.
[0239] The measurement results are shown in Table 1 below.
[0240] [Table 1]
[0241] As shown in the measurement results in Table 1, the light-transmitting film 100 according to the embodiment of the present invention has a power law slope, which is the slope of the graph, in the wavenumber range of 0.01 / Å to 0.1 / Å of an ultra-small angle X-ray scattering (U-SAXS) graph, which logarithmically represents scattering intensity versus wavenumber, in the range of -3.6 to -3.2. The light-transmitting film 100 according to the embodiment of the present invention having such a power law slope value has excellent light transmittance, low yellowness, and low haze. Furthermore, it can be confirmed that the fillers 120 in the light-transmitting film 100 according to the embodiment of the present invention are spaced apart from each other at an average interval of 20 nm or more.
[0242] <Example 2-1> A 1 L reactor was filled with 56.28 parts by weight of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 0.569 parts by weight (first content) of the solid powder polyamide-imide (light-transmitting resin powder) prepared in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to prepare a liquid light-transmitting resin solution.
[0243] Another 1 L reactor was filled with 37.9 parts by weight of silica dispersion 2A (SSD_330T, Ranco), which is a dispersion of silica particles having an average particle size of 10 to 15 nm at a content of 30% by weight in a DMAc (N,N-dimethylacetamide) solution (second solvent), and the temperature of the reactor was maintained at 25°C. The liquid light-transmitting resin solution prepared above was then slowly added using a cylinder pump for 1 hour to prepare a first mixture in which the silica dispersion and the light-transmitting resin solution were mixed.
[0244] 338.40 parts by weight of DMAc as a third solvent was added to the first mixed solution and stirred, and 63.832 parts by weight (second content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0245] The obtained second mixture liquid was cast. A casting substrate is used for casting. There is no particular limitation on the type of the casting substrate. As the casting substrate, a glass substrate, a stainless steel (SUS) substrate, a Teflon substrate, etc. can be used. According to an embodiment of the present invention, an organic substrate can be used as the casting substrate.
[0246] Specifically, the obtained second mixed liquid was applied and cast onto a glass substrate, and then dried with hot air at 120°C for 30 minutes to produce a film. The produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0247] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0248] As a result, a light-transmitting film 100 having a thickness of 50 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0249] <Example 2-2> A 1 L reactor was filled with 212.50 parts by weight of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 2.147 parts by weight (first content) of the solid powder polyamide-imide (light-transmitting resin powder) prepared in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to prepare a liquid light-transmitting resin solution.
[0250] Another 1 L reactor was filled with 143.1 parts by weight of silica dispersion 2A (SSD_330T, Ranco), which is a DMAc (N,N-dimethylacetamide) solution (second solvent) in which silica particles having an average particle size of 10 to 15 nm are dispersed at a content of 30% by weight, and the liquid light-transmitting resin solution produced above was slowly added using a cylinder pump for 1 hour while maintaining the temperature of the reactor at 25°C, producing a first mixture in which the silica dispersion and the light-transmitting resin solution were mixed.
[0251] 264.76 parts by weight of DMAc as a third solvent was added to the first mixed solution and stirred, and 62.254 parts by weight (second content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0252] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 120° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0253] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0254] As a result, a light-transmitting film 100 having a thickness of 50 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0255] <Example 2-3> A 1 L reactor was filled with 56.28 parts by weight of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 0.569 parts by weight (first content) of the solid powder polyamide-imide (light-transmitting resin powder) prepared in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to prepare a liquid light-transmitting resin solution.
[0256] Another 1 L reactor was charged with 37.9 parts by weight of silica dispersion 2B (SSK230U2, Ranco) in which silica particles having an average particle size of 30 nm were dispersed at a content of 30 wt% in a DMAc (N,N-dimethylacetamide) solution (second solvent), and the temperature of the reactor was maintained at 25° C., and the liquid light-transmitting resin solution prepared above was slowly added using a cylinder pump for 1 hour to prepare a first mixture in which the silica dispersion and the light-transmitting resin solution were mixed.
[0257] 338.40 parts by weight of DMAc as a third solvent was added to the first mixed solution and stirred, and 63.832 parts by weight (second content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0258] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 120° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0259] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0260] As a result, a light-transmitting film 100 having a thickness of 50 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0261] <Example 2-4> A 1 L reactor was filled with 136.62 parts by weight of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 1.38 parts by weight (first content) of the solid powder polyamide-imide (light-transmitting resin powder) prepared in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to prepare a liquid light-transmitting resin solution.
[0262] Another 1 L reactor was filled with 92 parts by weight of silica dispersion 2B (SSK230U2, Ranco), and the temperature of the reactor was maintained at 25° C. while the liquid light-transmitting resin solution prepared above was slowly added thereto using a cylinder pump for 1 hour to prepare a first mixture of the silica dispersion and the light-transmitting resin solution.
[0263] To the first mixed solution, 300.53 parts by weight of DMAc as a third solvent was added and stirred, and then 63.02 parts by weight (second content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Production Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0264] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 120° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0265] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0266] As a result, a light-transmitting film 100 having a thickness of 50 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0267] <Example 2-5> A 1 L reactor was filled with 16.83 parts by weight of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 0.17 parts by weight (first content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to produce a liquid light-transmitting resin solution.
[0268] Another 1 L reactor was filled with 17 parts by weight of silica dispersion 2C (50 nm SP-AD1, Admatechs), in which silica particles having an average particle size of 50 nm were dispersed at a content of 20 wt% in a DMAc (N,N-dimethylacetamide) solution (second solvent), and the temperature of the reactor was maintained at 25°C. The liquid light-transmitting resin solution prepared above was then slowly added using a cylinder pump for 1 hour to prepare a first mixture in which the silica dispersion and the light-transmitting resin solution were mixed.
[0269] To the first mixed solution, 351.33 parts by weight of DMAc as a third solvent was added and stirred, and then 64.23 parts by weight (second content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Production Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0270] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 120° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0271] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0272] As a result, a light-transmitting film 100 having a thickness of 50 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0273] < Reference example 2-1> A 1 L reactor was filled with 398.66 parts by weight of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 3.936 parts by weight (first content) of the solid powder polyamide-imide (light-transmitting resin powder) prepared in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to prepare a liquid light-transmitting resin solution.
[0274] Another 1 L reactor was charged with 262.4 parts by weight of silica dispersion 2A (SSD_330T, Ranco), which is a dispersion of silica particles having an average particle size of 10 to 15 nm at a content of 30 wt% in a DMAc (N,N-dimethylacetamide) solution (second solvent), and the liquid light-transmitting resin solution produced above was slowly added using a cylinder pump for 1 hour while maintaining the temperature of the reactor at 25°C, producing a first mixture in which the silica dispersion and the light-transmitting resin solution were mixed.
[0275] To the first mixed solution, 181.25 parts by weight of DMAc as a third solvent was added and stirred, and then 60.464 parts by weight (second content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0276] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 120° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0277] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0278] As a result, a light-transmitting film 100 having a thickness of 50 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0279] <Comparative Example 2-2> A 1L reactor was filled with 368.16 parts by weight of DMAc, and the temperature of the reactor was maintained at 10° C. and stirred for a certain period of time. 17 parts by weight of silica dispersion 2C (50nmSP-AD1, Admatechs) in which silica particles with an average particle size of 50 nm were dispersed at a content of 20% by weight in a DMAc (N,N-dimethylacetamide) solution (second solvent) was filled therein, and 64.4 parts by weight of the solid powder polyamide-imide (light-transmitting resin powder) produced in Production Example 1 was added and stirred for 1 hour. The mixture was then heated to 25° C. to produce a liquid light-transmitting resin mixture.
[0280] The resulting mixture was applied to a glass substrate, cast, and dried with hot air at 120° C. for 30 minutes to produce a film. The film was then peeled off from the glass substrate and fixed to a frame with pins.
[0281] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0282] As a result, a light-transmitting film 100 having a thickness of 50 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0283] < Reference example 2-3> A 1 L reactor was filled with 319.49 parts by weight of DMAc (first solvent), and the contents were stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 0.568 parts by weight (first content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Preparation Example 1 was added and stirred for 1 hour, and the temperature was raised to 25° C. to produce a liquid light-transmitting resin solution.
[0284] Another 1 L reactor was charged with 56.8 parts by weight of silica dispersion 2D (DMAc-ST-ZL, Nissan), in which silica particles having an average particle size of 70 nm were dispersed at a content of 20 wt% in a DMAc (N,N-dimethylacetamide) solution (second solvent), and the temperature of the reactor was maintained at 25° C., and the liquid light-transmitting resin solution prepared above was slowly added using a cylinder pump for 1 hour to prepare a first mixture in which the silica dispersion and the light-transmitting resin solution were mixed.
[0285] To the first mixed solution, 319.49 parts by weight of DMAc as a third solvent was added and stirred, and then 63.832 parts by weight (second content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Production Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0286] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 120° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0287] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0288] As a result, a light-transmitting film 100 having a thickness of 50 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0289] < Reference example 2-4> A 1 L reactor was filled with 56.23 parts by weight of DMAc (first solvent), and then stirred for a certain period of time while maintaining the temperature of the reactor at 10° C. Then, 0.568 parts by weight (first content) of the solid powder polyamide-imide (light-transmitting resin powder) prepared in Preparation Example 1 was added and stirred for 1 hour, and then the temperature was raised to 25° C. to prepare a liquid light-transmitting resin solution.
[0290] Another 1 L reactor was filled with 56.8 parts by weight of silica dispersion 2E (Y100SP-CD1, Admatechs), which is a dispersion of silica particles having an average particle size of 100 nm at a content of 20 wt% in a DMAc (N,N-dimethylacetamide) solution (second solvent), and the temperature of the reactor was maintained at 25° C., and the liquid light-transmitting resin solution prepared above was slowly added using a cylinder pump for 1 hour to prepare a first mixture in which the silica dispersion and the light-transmitting resin solution were mixed.
[0291] To the first mixed solution, 319.49 parts by weight of DMAc as a third solvent was added and stirred, and then 63.832 parts by weight (second content) of the solid powder polyamide-imide (light-transmitting resin powder) produced in Production Example 1 was added and stirred to produce a second mixed solution. The second mixed solution is a light-transmitting resin solution in which silica particles are dispersed.
[0292] The obtained second mixed liquid was applied and cast onto a glass substrate, and dried with hot air at 120° C. for 30 minutes to produce a film, and the produced film was then peeled off from the glass substrate and fixed to a frame with pins.
[0293] The frame with the film fixed thereto was placed in a vacuum oven and slowly heated from 100°C to 280°C for 2 hours, after which it was gradually cooled and separated from the frame to obtain a light-transmitting film. The light-transmitting film was then heat-treated again at 250°C for 5 minutes.
[0294] As a result, a light-transmitting film 100 having a thickness of 50 μm was completed, which contained a light-transmitting matrix 110 and silica-based filler 120 dispersed in the light-transmitting matrix.
[0295] <Measurement example> Examples 2-1 to 2-5 And reference examples 2-1 , Comparative Example 2-2, Reference Example 2-3 and Reference Example The light-transmitting film produced in 2-4 was subjected to the following measurements.
[0296] (1) Mean particle scattering coefficient
[0297] <Measurement equipment> Transmission electron microscope (TEM) (Manufacturer: Jeol / Model name: JEM-2100F)
[0298] <Measurement conditions> Accelerating voltage: 200 kV, magnification: 20,000x (20K)
[0299] <Cross-section processing> Microtome (Manufacturer: Leica / Model name: EM UC7) SPEED(mm / s):1mm / s FEED(nm):120nm Knife: DiATOME / Ultra 35 degrees
[0300] <Calculation method> Analyze using ImageJ as the image analysis program as follows.
[0301] 1) In Image type, switch to 8bit.
[0302] 2) In Process, use "Find maxima" to set the noise to 100, Output type to "Maxima within tolerance", and switch to "Exclude edge maxima" and "Light background".
[0303] 3) Perform "Fill holes" in Process Binary.
[0304] 4) Select “Watershed” from the Binary menu of Process.
[0305] 5) Drag the Rectangle and set the Area to 2250000~2500000 (excluding the area with the scale bar).
[0306] 6) Go to "Analyze" and select "Analyze particles". size(pixel 2 ):200-infinity, Circularity:0.0~1.0
[0307] The area of each particle is summed and divided by the number of particles to obtain the "average particle area."
[0308] 7) From the image obtained with a transmission electron microscope (TEM), measure the straight segment of the scale bar to determine the "length per pixel (nm)."
[0309] 8) The average particle area (pixel) obtained from “6”) is converted to an area in metric units (SI units) using the length per pixel in “7”) to obtain the average particle size.
[0310] <Expression 3> JPEG0007620078000011.jpg15170
[0311] The average particle size of the filler 120 calculated using transmission electron microscopy (TEM) and ImageJ was used as the particle size D of the filler 120 in Equation 2.
[0312] Using the particle size D of the filler 120 thus obtained, the average particle scattering coefficient of the filler 120 is calculated according to Equations 1 and 2.
[0313] <Expression 1> TIFF0007620078000012.tif2158
[0314] X in Equation 1 k can be calculated from the following equation 2.
[0315] <Expression 2> X k =πD / λ k
[0316] In formulas 1 and 2, k is an integer of 1 to 38.
[0317] Also, in Equation 2, λ k = (37 + k) × 10 nm, and D is the particle size of the filler 120 measured by transmission electron microscopy (TEM).
[0318] (2) Light transmittance (%): The average light transmittance was measured at wavelengths of 360 to 740 nm using a Spectrophotometer (CM-3700D, KONICA MINOLTA) according to standard ASTM E313.
[0319] (3) Yellowness: Yellowness was measured according to standard ASTM E313 using a Spectrophotometer (CM-3700D, KONICA MINOLTA).
[0320] (4) Haze: The manufactured light-transmitting film was cut into a piece of 50 mm x 50 mm, and was measured five times according to ASTM D1003 using a haze meter (model name: HM-150) made by MURAKAMI, and the average value was taken as the haze value.
[0321] (5) Modulus: The modulus of the light-transmitting film was measured using an Instron universal tensile tester according to the ASTM D885 method.
[0322] - Measurement criteria within 3 hours after film production - Road Cell 30KN, Grip 250N. - Sample size: 10 x 50 mm, tensile speed: 25 mm / min
[0323] The measurement results are shown in Table 2 below.
[0324] [Table 2]
[0325] As shown in the measurement results in Table 2, it can be confirmed that the light-transmitting film 100 according to an embodiment of the present invention has an average particle scattering coefficient of 0.35 or less, and thus has excellent light transmittance, low yellowness, and low haze. [Explanation of symbols]
[0326] 100: Light-transmitting film 110: Light-transmitting matrix 120: Filler 200:Display device 501: Display panel
Claims
1. A step of preparing a light-transmitting resin powder, which is a powder of a light-transmitting resin; dissolving a first content of the light-transmitting resin powder in a first solvent to prepare a light-transmitting resin solution; preparing a filler dispersion in which a filler is dispersed in a second solvent; mixing the filler dispersion and the light-transmitting resin solution to prepare a first mixture; adding a third solvent to the first mixture; and adding and dissolving a second content of the light-transmitting resin powder in the first mixture to prepare a second mixture, the first content of the light-transmitting resin powder is 0.5 to 10% by weight of the filler, the third solvent is the same as the first solvent; the light-transmitting resin contains imide repeating units and amide repeating units, The average particle size of the filler is 5 to 50 nm; A method for producing a light-transmitting film, wherein the content of the filler is 5 to 50% by weight based on the total weight of the light-transmitting film.
2. 2. The method for producing a light-transmitting film according to claim 1, wherein the second content of the light-transmitting resin powder is 10 to 200 times the first content.
Citation Information
Patent Citations
Polyimide film
WO2017014277A1